AN ANALYSIS ON FACTORS CAUSING UNDERGRADUATE STUDENTS’ DIFFICULTIES IN WRITING THESIS - Sariyanto, .; Supardi, Iwan; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to find out the most causing factor of undergraduate students’ difficulties in writing thesis in the English Education Study Program of FKIP Tanjungpura University Pontianak. Descriptive research design was used in this research. 28 students were chosen as the sample and selected by using purposive sampling. The data was collected by using questionnaire with 31 items designed on a five-point likert-type scale to capture students’ opinion about the causing factors of their difficulties in writing thesis. Data analysis shows that basic knowledge of thesis main components factor has percentage 27.68%, process of consultation factor has percentage 26.04%, psychological factor has percentage 25.25%, while economic factor has percentage 21.03%. Therefore, it is concluded that basic knowledge of thesis main component factor is the most causing factor of students’ difficulties in writing thesis.   Keywords: factors, difficulties, thesis     Abstrak: Tujuan penelitian ini adalah untuk menemukan faktor yang paling menyebabkan mahasiswa Prodi Bahasa Inggris FKIP Universitas Tanjungpura kesulitan dalam menulis skripsi. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. 28 siswa dipilih menjadi sample menggunakan sample purposif. Data dikumpulkan menggunakan angket yang berjumlah 31 item didesain berdasarkan 5 poin skala likert untuk menangkap opini mahasiswa mengenai faktor-faktor yang menyebabkan mereka kesulitan dalam menulis skripsi. Data analisis menunjukan bahwa faktor pengetahuan dasar dari komponen utama skripsi mendapat persentase 27.68%, faktor proses konsultasi mendapat persentase 26.04%, faktor psikologi mendapat persentase 25.25%, sedangkan faktor ekonomi mendapat persentase 21,03%. Oleh karena itu, disimpulkan bahwa faktor pengetahuan dasar dari komponen utama skripsi adalah faktor yang paling menyebabkan mahasiswa kesulitan dalam menulis skripsi.   Kata kunci: faktor, kesulitan, skripsi